ENTREPRENEURIAL MARKETING EDUCATION AND GRADUATE‘S CAPACITY FOR SELF-EMPLOYMENT IN SOUTH-WEST, NIGERIA - Eniola Alao, Abiodun; Abiola , Moshood (International Journal of Multidisciplinary Research and Studies, 2019)
This study looked into the relationship between entrepreneurial marketing education and graduates’ capacity for self-employment in the southwest, Nigeria. The study unit for this research is the Universities and Polytechnic graduates in South West, Nigeria. A cross-sectional descriptive survey research design was used to investigate how entrepreneurial marketing education would have a significant effect on graduates’ capacity to become self-employed in specialized fields of marketing. The population of the study consisted of three hundred and forty-seven (347) graduating students of marketing in 9 tertiary institutions that offer marketing in southwest, Nigeria. Using questionnaire administration as a data collection technique, a total enumeration (census) of the population was sampled. Data collected were analyzed using both descriptive and inferential statistics. Findings of the study hypothesis one revealed that there is a significant positive relationship between entrepreneurial marketing education and entrepreneurial digital marketing (r = .696, n = 329, p <.005). Similarly, the study’s second hypothesis showed that there is a significant positive relationship between entrepreneurial marketing education and entrepreneurial event marketing (r =.897, n =329, p<.05). The third hypothesis further showed a significant positive relationship between entrepreneurial marketing education and entrepreneurial merchandising (r = .636, n = 329, p = .005).The study concluded that there is a significant positive relationship between entrepreneurial marketing practices and graduates’ capacity for self-employment in Southwest, Nigeria.